Study on ecotourism development in Olele Coastal Area, Bone Bolango Regency, Gorontalo Province - Mahale, Moch Machtino A; Mandagi, Stephanus V; Lasut, Markus T (AQUATIC SCIENCE & MANAGEMENT, 2018)
Title (Bahasa Indonesia): Studi pengembangan ekowisata di Kawasan Pesisir Olele, Kabupaten Bone Bolango, Provinsi Gorontalo The purpose of this research is to evaluate coral reef and reef fish condition in coastal waters of Olele village; to study the feasibility of ecotourism development in that area and to formulate ecotourism development strategy. This study reveals that theecological condition of Olele waters is good, and it was shown bythe average coral cover which ishigher than 50%. Similarly, fish species is in very high abundance, with a total of 36 species and a total number of more than 12.993 fish, wherePseudanthias tukais the highest population. In terms of ecotourism feasibility development, total of Pirkins Score were 3,2, andthis can be categorized as moderate, meaning that Olele coastal area can be developed as ecotourism area. Finally, strategies for ecotourism development of Olele coastal area are; a) using Olele coastal resources for ecotourism destiny by promoting conservation values, b) infrastructure ecotourism development needs to be improved, c) integratrated ecotourism management policies should be included in policy for development of Kabupaten (disrict) government level; d) development of ecotourism need to cooperation between district government and private sectors.Tujuan penelitian ini adalah mengevaluasi kondisi terumbu karang dan ikan karang yang berada di perairan pesisir Olele, mengkaji kelayakan pengembangan ekowisata di kawasan pesisir Olele dan merumuskan strategi pengembangan kawasan ekowisata. Dari hasil penelitian dan analisis data, kondisi ekologi perairan Olele berada pada kategori baik: karang pada stasiun 1 rata-rata memiliki tutupan karang hidup >50%, artinya bahwa keragaman karang tinggi. Sama halnya dengan spesies ikan, jumlah species sebanyak 36 spesies dan total jumlah individu sebanyak 12.993 dimana spesies terbanyak yaitu Pseudanthias tuka. Selanjutnya analisis kelayakan pengembangan ekowisata, total nilai scoringPirkins 3,2 atau berada pada level moderat, artinya dapat dikembangkan menjadi kawasan ekowisata. Untuk pengembangan ekowisata dikawasan Pesisir Olele, di rekomendasikan beberapa strategi yaitu; a) memanfaatkan sumberdaya pesisir sebagai target utama ekowisata dengan menjunjung nilai-nilai konservasi, b) infrastruktur penunjang pengembangan ekowisata perlu dibenahi, c) perlu dibuat kebijakan pengelolaan dan pengembangan ekowisata secara terpadu antar pemerintah daerah, d) adanya kerja sama antara pemerintah dan pihak swasta dalam hal pengelolaan objek wisata.